Towards Optimized K Means Clustering using Nature-inspired Algorithms for Software Bug Prediction (Global Journal of Computer Science and Technology, 2023)
In today s software development environment the necessity for providing quality software products has undoubtedly remained the largest difficulty As a result early software bug prediction in the development phase is critical for lowering maintenance costs and improving overall software performance Clustering is a well-known unsupervised method for data classification and finding related patterns hidden in datasets
Keywords: data clustering; K-means algorithm; Nature-inspired algorithms; software bug detection; coral reefs